School Size Choices: Comparing Small and Large School Strengths - Fairman, Janet (Maine Policy Review, 2003)
Janet Fairman discusses the thorny issue of school quality, suggesting that small schools have certain strengths compared to larger schools. Data from her study of small high schools in Maine, as well as research literature, suggest that compared to large schools, small schools allow for greater personal attention to students, have greater flexibility in scheduling, programming and instructional decisions, and often have stronger school-community connections that support student achievement and serve important community needs. Using quantitative measures of quality, Fairman notes that school size alone explains very little of the variation in 11th grade Maine Educational Assessment (MEA) scores, while on other measures there are only small differences based on school size. She suggests that as school systems are redesigned for greater cost efficiency, we should be mindful of the strengths of both small and large high schools and make these strengths part of all high schools, no matter their size.
Keywords: Maine; school size